Organizational support and institutional environment for entrepreneurship development - Andjelic, Slavica; Cukanovic Karavidic, Marija; Karavidic, Slavko (International Review, 2015)
Enterprise and Entrepreneurship are naturally connected and linked to the man, hisindividuality and dynamism. A man develops his entrepreneurial skills in the company isorganized so that it represents a healthy environment for the development ambitions. Theonly reliable sources of progress and prosperity are the work and entrepreneurship. It haslong been in the world economic literature of special importance in the process ofrestructuring the economy in economic growth and development of countries in transitionis given to the establishment of new enterprises and entrepreneurship development. I do notbelieve that it is a new form of paradigm, however, the fact remains that a large shift in theliterature devoted to the economy of transition. Entrepreneurship means a special kind ofwork which aims to emphasize the great importance of possessing human creative,organizational and management capacity. The term enterprise wants to emphasize theimportance of possessing an exceptional human creative ability. It appears as acombination of dynamic development of ideas, talent, capital, knowledge and risk.